Extradigestive Manifestations of Helicobacter Pylori Infection - An Overview 2016
DOI: 10.5772/63826
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Diabetes Mellitus

Abstract: Helicobacter pylori colonizes the stomach and causes chronic gastritis, which most often remains asymptomatic. However, in a small proportion of infected persons, it causes peptic ulcers and gastric cancer. We reviewed recent evidence of the association between H. pylori infection and diabetes mellitus DM . Numerous studies have shown a positive association between H. pylori infection and DM, however, findings are still conflicting. Such a link is biologically plausible, given the importance of the stomach in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…The literature regarding the association between H. pylori and diabetes risk is inconsistent, with reports of positive, null and negative associations [4][5][6]. A published meta-analysis systematically reviewed the association between H. pylori Table 2 Association between H. pylori infection and risk of developing diabetes ( No., number Table 3 Association between persistent H. pylori infection and risk of developing diabetes No., number infection and diabetes based on observational studies and drew the conclusion that there was a trend toward more frequent H. pylori infection in individuals with diabetes [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature regarding the association between H. pylori and diabetes risk is inconsistent, with reports of positive, null and negative associations [4][5][6]. A published meta-analysis systematically reviewed the association between H. pylori Table 2 Association between H. pylori infection and risk of developing diabetes ( No., number Table 3 Association between persistent H. pylori infection and risk of developing diabetes No., number infection and diabetes based on observational studies and drew the conclusion that there was a trend toward more frequent H. pylori infection in individuals with diabetes [4].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have also revealed that H. pylori infection may have a wider ranging impact on health through its extragastrointestinal effects [3]. Specifically, this includes an association between H. pylori infection and diabetes [4][5][6], a harmful metabolic disease with rapidly increasing prevalence worldwide, particularly over the past 30 years [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation